Making the (letter) grade: The incentive effects of mandatory pass/fail courses - Kristin F. Butcher; Patrick J. McEwan; Akila Weerapana (Federal Reserve Bank of Chicago, 2022)
In Fall 2014, Wellesley College began mandating pass/fail grading for courses taken by first-year, first-semester students, although instructors continued to record letter grades. We identify the causal effect of the policy on course choice and performance, using a regressiondiscontinuity-in-time design. Students shifted to lower-grading STEM courses in the first semester, but did not increase their engagement with STEM in later semesters. Letter grades of first-semester students declined by 0.13 grade points, or 23% of a standard deviation. We evaluate causal channels of the grade effect-including sorting into lower-grading STEM courses and declining instructional quality-and conclude that the effect is consistent with declining student effort.
Keywords: I23; 330; Higher Education; Grading Policy; Bildungsverhalten; Anreiz; Hochschule; Studierende; Studium; MINT-Fächer; USA